A. MUÑOZ GARCÍA, L. VELÁSQUEZ, M. LIUZZO (Eds.), Cursus Philosophicus Antonii Iosephi Suaretii de Vrbina. Logica. - Nava Contreras, Mariano José (Cuadernos de Filología Clásica. Estudios Latinos, 1997)
Sin resumen